Water requirement of drip irrigated sugarcane in the Coastal Lands of Alagoas - Silva, Samuel; Neto, Jose Dantas; Teodoro, Iedo; Souza, Jose L. de; Lyra, Guilherme B.; Santos, Marcos A. L. dos [UNESP] (Univ Federal Campina Grande, 2015)
Water is a natural resource that has been the subject of much debate about its use and availability in recent years. In the agricultural sector, the volume of water needed for irrigation is calculated based on the losses incurred by evaporation and transpiration. Thus, this study aimed to determine the maximum and actual evapotranspiration of drip irrigated sugarcane. The data for this study were obtained in an experiment conducted in the region of Rio Largo (Alagoas, Brazil), with seven irrigation treatments (0; 25; 50; 75; 100; 125 and 150% of the reference evapotranspiration - ET0), in three production cycles from January 2009 to February 2012. The actual evapotranspiration (ETr) was estimated by dual K-c. The mean ETr in the maximum growth phase of the three cycles ranged from 1.73 at 5.04 mm d(-1) in the treatments with 0 and 150% of ET0, respectively. The sugarcane, in rainfed conditions in this region, is exposed to average climatic risk, according to the classification proposed in the literature.
Keywords: Saccharum spp.; water storage in the soil; moisture deficit